Compilation of document-information resources in libraries (Based on the work experience of the National Library named after M.F. Akhundov) - Manafova, Ulduz (Technium Social Sciences Journal, 2022)
In the article, the concept of assembly is explained scientifically and theoretically. The article also analyzed the quantitative indicators of the information resources in the fund of the National Library named after Akhundov for different years. Brief information about the history of the Akhundov National Library was given, the general methodology of the collection of library collections was shown, and the layout forms used in the library collection were noted.